Rural indigenous students in Peruvian Urban higher education: interweaving ecological systems of coloniality, community, barriers, and opportunities. Issue 1 (2nd January 2022) - Johnson, Kayla M.; Levitan, Joseph
ABSTRACT: In Peru, Indigenous students from rural communities must often migrate to urban areas to access higher education. Navigating to and through urban higher education is a complex task where Peru's oppressive colonial legacies intertwine with students' community values, resources, and strengths. How can we more deeply understand the interconnecting systems that oppress and support rural Indigenous students, and how can we mobilize these understandings to reimagine higher education? In this paper, we use photo-cued interviewing and ecological systems theory to 1) make sense of rural Indigenous students' experiences as they navigate to and through higher education in urban areas and 2) uncover levers for systemic change to improve higher education policy and practice. In doing so, we expand beyond a two worlds perspective of Indigenous educational experiences to offer a more holistic view on coloniality and Indigenous resilience in higher education.